2013
DOI: 10.3389/fonc.2013.00294
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Achilles Heel of FOXP3

Abstract: FOXP3 is a multifaceted transcription factor with a major role in the control of immune homeostasis mediated by T regulatory cells (Treg). The immunoregulatory function of FOXP3 may hinder the induction of immune responses against cancer and infectious agents, and thus, development of inhibitors of its functions might give new therapeutic opportunities for these diseases. But also, FOXP3 is an important tumor suppressor factor in some types of cancers, and therefore, understanding the structure and function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 98 publications
0
17
0
Order By: Relevance
“…Many of the functions of FOXP3 are clearly regulated by the interactions with these cofactors, contributing importantly to establishment of the Treg signature and also to FOXP3 functions (reviewed in Ref. 41). Among the increasing number of transcription factors able to bind to FOXP3, we have focused on NFAT/FOXP3 interaction, which has been shown to be crucial to repress expression of IL-2, upregulate expression of the Treg markers CTLA4 and CD25, and confer suppressor function (18).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the functions of FOXP3 are clearly regulated by the interactions with these cofactors, contributing importantly to establishment of the Treg signature and also to FOXP3 functions (reviewed in Ref. 41). Among the increasing number of transcription factors able to bind to FOXP3, we have focused on NFAT/FOXP3 interaction, which has been shown to be crucial to repress expression of IL-2, upregulate expression of the Treg markers CTLA4 and CD25, and confer suppressor function (18).…”
Section: Discussionmentioning
confidence: 99%
“…HIV transcriptional downregulation could be associated with NF-κB-dependent and -independent mechanisms ( 63 ), as well as to the Foxp3-dependent inhibition of NFAT activity. It was shown that Foxp3 decreases the binding of NFAT2 to the HIV promoter in vivo by its capacity to sequestrate it ( 61 , 64 ).…”
Section: Treg Immune-modulation and Mechanisms Of Actionmentioning
confidence: 99%
“…previous studies including ours on psoriasis and squamous cell carcinoma (10,16,17). However, few studies showed that the numbers of FOXP3 + Tregs were reduced or unchanged after UV irradiation (30,31). These differences may be explained by the individual difference, disease status or differences in UV exposure conditions.…”
Section: Discussionmentioning
confidence: 99%